Distribution of T-lymphocyte subsets in patients with vascular diseases - Horváth, M; Jovanovich, N; Kádár, K; Györffy, G (Cor et vasa, 1984)
The distribution of T-lymphocyte subsets was studied in patients with myocardial infarction, peripheral arterial disease and thrombophlebitis. The percentage of SRBC-rosette forming active - E[A] and total - E[T] lymphocytes in patients and healthy controls was not different. A significant increase in the percentage and number of theophylline-resistant - E[Thr] and T[M] - helper cells was found in patients with myocardial infarction or with thrombophlebitis, and a moderate elevation was observed in patients with peripheral arterial disease. No difference between patients and controls could be shown in the percentage and number of theophylline-sensitive E[Ths] and T[G] - suppressor cells. The imbalance of T-lymphocyte subsets is thought to be the consequence of sensitization against vascular tissues during vascular diseases.
Keywords: Myocardial Infarction; Thrombophlebitis; regulační T-lymfocyty; T-lymfocyty; T-Lymphocytes, Helper-Inducer; T-Lymphocytes, Regulatory; Humans; tvorba rozet; Arterial Occlusive Diseases; T-Lymphocytes; lidé; arteriální okluzní nemoci; T-lymfocyty pomocné-indukující; počet leukocytů; infarkt myokardu; tromboflebitida; Leukocyte Count; Rosette Formation